Clinacanthus nutans extracts are antioxidant with antiproliferative effect on cultured human cancer cell lines - Yong, Yoke Keong; Tan, Jun Jie; Teh, Soek Sin; Mah, Siau Hui; Ee, Gwendoline Cheng Lian; Chiong, Hoe Siong; Ahmad, Zuraini (Hindawi Publishing Corporation, 2013)
Clinacanthus nutans Lindau leaves (CN) have been used in traditional medicine but the therapeutic potential has not been explored for cancer prevention and treatment. Current study aimed to evaluate the antioxidant and antiproliferative effects of CN, extracted in chloroform, methanol, and water, on cancer cell lines. Antioxidant properties of CN were evaluated using DPPH, galvinoxyl, nitric oxide, and hydrogen peroxide based radical scavenging assays, whereas the tumoricidal effect was tested on HepG2, IMR32, NCL-H23, SNU-1, Hela, LS-174T, K562, Raji, and IMR32 cancer cells using MTT assay. Our data showed that CN in chloroform extract was a good antioxidant against DPPH and galvinoxyl radicals, but less effective in negating nitric oxide and hydrogen peroxide radicals. Chloroform extract exerted the highest antiproliferative effect on K-562 (91.28 ± 0.03%) and Raji cell lines (88.97 ± 1.07%) at 100  μ g/ml and the other five cancer cell lines in a concentration-dependent manner, but not on IMR-32 cells. Fourteen known compounds were identified in chloroform extract, which was analysed by gas chromatography-mass spectra analysis. In conclusion, CN extracts possess antioxidant and antiproliferative properties against cultured cancer cell lines, suggesting an alternate adjunctive regimen for cancer prevention or treatment.